Analysis of rural students’ pursuit of community college using community cultural wealth: not everyone has a yellow brick road - Gannon, Jenna Leigh (Kansas State University, 2023)
Rural students’ college attendance rates continue to lag behind their non-rural counterparts (Ardoin, 2018; Barr, 2018; Byun et al., 2012; Byun et al., 2015; Byun et al., 2017; Friesen & Purc-Stephenson, 2016; Hlinka et al., 2018; Longhurst, 2014; McDonough et al., 2010; Morton et al., 2018; Tieken, 2016). While the body of research surrounding the pursuit of college for rural students is expanding, much of it focuses on deficit perspectives or in a few select geographic regions of the United States (Ardoin, 2018; Barr, 2018; Chenoweth & Galliher, 2004; Harris, 2013; Hlinka et al., 2015; Howley et al., 2013; Morton et al., 2018; Sharp et al., 2020; Theodori & Theodori, 2015; Tieken, 2016; Wright, 2012). This research utilized creative nonfiction to give voice to underserved populations in rural Kansas, building from Yosso’s (2005) strengths-based community cultural wealth. The research documented that aspirational capital was directly linked to college knowledge. Rural cultural wealth facilitators were key to the development of community cultural wealth and especially aspirational capital within that construct. The participants operationalized their aspirations to seek out college knowledge. The study concludes with practical implications for community colleges as well as suggestions for further research.
Keywords: Community cultural wealth; Rural students; Narrative inquiry; College access; Community colleges; Creative nonfiction